Evaluation of the Cuticle Bleeding Time in Canine Haemophilia A - Pijnappels, M I M; Briët, E; Zwet, G Th van der; Huisden, R; Tilburg, N H van; Eulderink, F (Thrombosis and Haemostasis, 1986)
In this paper we describe our clinical experience and results with the cuticle bleeding time test in a colony of cross-bred Labrador retrievers with severe haemophilia A. The dogs have a severe bleeding tendency with a high incidence of fatal haemorrhages in the central nervous system. Homozygous females appeared to be especially prone to this lethal complication. Factor VIII recovery and half-life determinations yielded results similar to the data from human studies. The cuticle bleeding time proved to be a good measure of the coagulation defect. The prolongation of the bleeding time could be completely abolished by administration of 10 to 15 units of canine factor VIII per kg body weight. We conclude that the cuticle bleeding time in canine haemophilia provides us with a suitable model for the in vivo study of new therapeutic materials.
Keywords: Haemophilia A; Dogs; Cuticle bleeding time